2006
DOI: 10.1038/sj.ijo.0803200
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to body fat gain in ‘double-muscled’ mice fed a high-fat diet

Abstract: Objective: To determine if myostatin deficiency attenuates body fat gain with increased dietary fat intake. Methods: Normal and myostatin-deficient mice were fed control (8-10 kcal %fat) and high-fat (HF) (45 kcal %fat) diets for a period of 8 weeks, starting at 2 months of age. Body composition, including percent body fat, lean mass, and fat mass, were measured using DXA. Serum adipokines were measured using a Beadlyte assay. Results: Two-factor ANOVA revealed significant treatment  genotype interactions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
33
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 14 publications
10
33
2
Order By: Relevance
“…Myostatin knock-out (KO) mice offered high-fat diets are resistant to gains in body fat [14], [15], and although this effect may be secondary to the increases in lean body mass, myostatin had direct effects on adipocyte differentiation [16], [17]. Furthermore, blocking myostatin increased the functional capacity of brown adipose tissue (BAT) [18] and may even drive the browning of white adipose tissue through the up-regulation of BAT-specific genes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Myostatin knock-out (KO) mice offered high-fat diets are resistant to gains in body fat [14], [15], and although this effect may be secondary to the increases in lean body mass, myostatin had direct effects on adipocyte differentiation [16], [17]. Furthermore, blocking myostatin increased the functional capacity of brown adipose tissue (BAT) [18] and may even drive the browning of white adipose tissue through the up-regulation of BAT-specific genes [19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in vitro studies with various mesenchymal adipocyte progenitor cells are again highly controversial because myostatin has been demonstrated to both inhibit and stimulate their differentiation into mature adipocytes (29 -33). Resolving this controversy has clinical implications because attenuating myostatin both prevents and reverses obesity in different animal models and can even improve insulin sensitivity (26,28,34,35). Thus, novel myostatinantagonizing therapeutics, which are currently being developed (36 -38), could potentially be used to treat type 2 diabetes in addition to muscle-related disorders.…”
mentioning
confidence: 96%
“…Furthermore, myostatin-null mice and myostatin propeptide-overexpressing Tg mice were used to study the effects of myostatin inhibition on obesity (10,14,24,41,42). These studies revealed that the inhibition of myostatin decreased adipose tissue accumulation and improved diet-induced obesity and genetic diabetes/obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of myostatin by gene disruption prevents an agerelated increase in adipose tissue mass and partially attenuates the obese and diabetic phenotypes (14,24). The serum leptin concentration and adipose tissue leptin mRNA expression were lower in myostatin null mice than in wild-type mice (24).…”
mentioning
confidence: 95%